EFFECT OF ASN COMPETENCY, ORGANIZATIONAL COMMITMENT, WORK ENVIRONMENT TO THE SATISFACTION OF ASN AND PERFORMANCE IN THE ENVIRONMENT OF THE HOUSING OF THE HOUSING AND SETTLEMENT AREAS OF BANGKALAN REGENCY - murgianto, murgianto (Archives of Business Research, 2021)
This research is to examine and analyze the competence of the work environment commitment of ASN Job Satisfaction. The demands of organizations to obtain, develop and maintain quality human resources are increasingly pressing in accordance with the dynamics of an ever-changing environment. In the context of efforts to achieve organizational goals. Improved employee performance individually will encourage the overall performance of human resources, which is reflected in improved performance This research. Using research models (jobfunction). Data extracted from the target or research subject is data about individual orientation, in the form of competency, commitment, work environment and performance, identified as many as 4 (four) variables to be examined, including: 1) ASN Competency, 2) Organizational Commitment, (3) Environment Work, (4) ASN Job Satisfaction and (4) ASN Performance. Respondents used as a sample of 77 respondents using the Smart PLS Algorithm Boostrapping report. The results of the study came to the conclusion of the Algorithm Boostrapping report is a test to prove the level of significance of the hypothesis proposed by researchers. Output Boostrapping Algorithm shows that the effect of ASN job satisfaction on ASN performance is influential with a T-statistic of 9,531> 1.96. The original sample estimate value is 1,058, which shows that the direction of the relationship between ASN job satisfaction and ASN performance is positive.